Women’s Representations in Moroccan Cinema: A Comparative Analysis of Wechma (1970) and Deux Femmes Sur La Route (2007) - Akrachi, Nadir; Boutkhil, Soumia (Integrated Journal for Research in Arts and Humanities, 2024)
The present study aims at making a comparative analysis of the representation (s) of women as well as political discourses addressed in Moroccan films mainly seventies films and recently made films. To this end, two films were chosen to be analysed. These films are Wechma (Traces, 1970) directed by Hamid Bennani, and Deux Femmes sur la Route (Two Women on the Road, 2007) by Farida Bourquia. Qualitative content analysis was used as the main data analysis method to compare the films. The choice of using qualitative content analysis did not come at random, but it is because of the fact that the study was qualitatively approached. The results obtained indicated that women’s representations still need improvements. Women in the films are depicted in different ways. In Wechma (Traces, 1970), women are described as ‘subalterns’ occupying secondary roles in their society. However, Bourquia’s Deux Femmes sur la Route (Two Women on the Road, 2007) depicts two different examples of women. One is traditional and still restricted to her society’s norms, and another is independent and emancipated from society’s restrictions.